MATERIAL RELIABILITY STUDY OF HIGH-SPEED SMALL CRAFT UNDER WAVE LOAD - Amalia Ika Wulandari; Alamsyah A; Suardi S; Wira Setiawan; Muhammad Uswah Pawara; Andi Mursid Nugraha Arifuddin; Husein Syahab (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2024)
This study focuses on analyzing the structural characteristics of a small craft constructed using aluminum alloy compared with sandwich material structure. High speed vessels are designed to address key performance challenges such as vessel motion, engine efficiency, fuel consumption, and cargo capacity. However, to endure extreme wave induced loads, enhancement of vessel’s the structural strength is essential, especially in critical areas like the midship section. Analytical models and probabilistic methods are employed to predict structural performance under both constant and random wave loading conditions. Aluminum alloys are commonly chosen for fast boat construction due to their high strength to weight ratio and corrosion resistance. To evaluate structural behavior, simulations are carried out under varying wave heights and directions, providing insight into how the vessel performs in challenging marine environments. Load analysis is conducted using diffraction theory and the JONSWAP spectrum equation to determine the maximum bending moments experienced by the hull. The results show that both aluminum and sandwich structures exhibit similar reliability thresholds under wave-induced loading, but the sandwich structure consistently performs slightly better, with approximately 0.10% higher reliability. This suggests that sandwich materials offer improved structural integrity, making them the more suitable choice for high-speed small craft operating in wave conditions up to 2 meters. This analysis contributes to a deeper understanding of the reliability and performance of these materials, offering valuable guidance for designing and constructing high Small Crafts that perform efficiently and safely in demanding maritime operations.